The Control of an Upper-Limb Exoskeleton by Means of a Particle Swarm Optimised Active Force Control for Motor Recovery - Anwar, P. P. Abdul Majeed; Zahari, Taha; Ismail, Mohd Khairuddin; Mohd Yashim, Wong Paul Tze; Muhammad Amirul, Abdullah; Mohd Azraai, M. Razman (Springer, 2017)
This paper presents the modelling and control of a two degree of freedom upper extremity exoskeleton for rehabilitation. The Euler-Lagrange formulation was employed to obtain the dynamic modelling of both the anthropometric based human upper limb as well as the exoskeleton that comprises of the upper arm and the forearm. A proportionalderivative (PD) architecture is employed to investigate its efficacy in performing joint-space control objectives namely the flexion/extension of the elbow joint as well as the forward adduction/abduction on the shoulder joint. An intelligent active force control (AFC) optimised by means of the Particle Swarm Optimisation (PSO) algorithm is also incorporated into the aforementioned controller to examine its effectiveness in compensating disturbances. It was found from the study that the PD- PSOAFC performed well against the disturbances introduced into the system without compromising its tracking performances as compared to the classical pure PD counterpart.